2016
DOI: 10.1002/cssc.201600090
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Adsorption Properties of Carbon Nanotubes and Platinum Nanoparticles from a New Ammonium‐Ethylimidazolium Chloroplatinate Salt

Abstract: Self-supporting membranes built entirely of carbon nanotubes have been prepared by wet methods and characterized by Raman spectroscopy. The membranes are used as supports for the electrodeposition of Pt nanoparticles without the use of additional additives and/or stabilizers. The Pt precursor is an ad hoc synthesized ammonium-ethylimidazolium chloroplatinate(IV) salt, [NH3 (CH2 )2 MIM)][PtCl6 ]. The Pt complex was characterized using NMR spectroscopy, XRD, ESI-MS, and FTIR spectroscopy. The interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Additionally, alternative electrochemically irreversible probes such as NAD + and ascorbic acid have been used to measure the surface area of commercial SPEs using CV [ 19 ]. Moreover, Terranova et al have utilised dilute H 2 SO 4 for determining the area of a MWCNT-PtNP modified electrode using a both CV and CC methods [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, alternative electrochemically irreversible probes such as NAD + and ascorbic acid have been used to measure the surface area of commercial SPEs using CV [ 19 ]. Moreover, Terranova et al have utilised dilute H 2 SO 4 for determining the area of a MWCNT-PtNP modified electrode using a both CV and CC methods [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of noble metal surface layers can be controlled by electronic means, such as through electro‐deposition methods, adjusting the potential/current density and time, [42] as well as selecting platinum precursor salts and adjusting the electrolyte, [23c] to achieve control over the number of noble metal shell layers. Crooks and his colleagues have developed an electrochemical approach known as hydride‐terminated electrodeposition, which allows for the deposition of a single Pt monolayer on bulk‐phase Au surfaces (Figure 2a).…”
Section: Driving Forces Of Strain On Noble Metal Surface and Characte...mentioning
confidence: 99%
“…Orlanducci and colleagues fabricated self‐supporting membranes constructed solely from carbon nanotubes using wet methods. These membranes serve as substrates for the electrodeposition of Pt NPs, eliminating the need for supplementary additives and/or stabilizers [23c] . Recent work by our group has demonstrated that synthesizing micron‐sized Pt‐WC/CNT catalysts via a self‐assembly route, which are both superhydrophilic and feature a coronavirus‐like structure, leads to outstanding intrinsic activity and efficient bubble transfer properties (Figure 10b–d).…”
Section: Practical Use: Materials Stability and Electrode Activitymentioning
confidence: 99%